Fenomena Wahyu Al-Quran - Haq, Sansan Ziaul (Prodi Ilmu Al-Qur'an dan Tafsir Fakultas Ushuluddin Institut Ilmu Al-Qur'an (IIQ) Jakarta, 2019)
Some Western scholars argue that the Qur?an is a historical text that reflects Mu?ammad?s reflection on the socio-cultural dynamics of seventh-century Arab society. In the hands of several modern Muslim scholars, the assumption of the historicity of the Qur?an is used as a basis for contextual reinterpretation, although in general they still acknowledge its divinity. This paper intends to conceptualize the phenomenon of Qur?anic revelation through an analysis of the chronology of its revelation as explained in s?rah nabawiyyah. Through this analysis, it can be concluded that the process of Qur?anic revelation was external, did not originate from the Prophet Muhammad?s idea. Its revelation is a transcendent process as well as the concept of revelation understood in every religious tradition, even though it is intended for human benefit. The assumption of the historicity of Qur?anic revelation does not get strong support from s?rah?s data.